W-ZrC composites prepared by reactive melt infiltration of Zr2Cu alloy into partially carburized W preforms. (September 2017) - Wang, Dong; Chen, Lei; Wang, Yu-Jin; Huo, Si-Jia; Ouyang, Jia-Hu; Zhou, Yu
Abstract: W-ZrC composites without residual WC have been prepared for the first time by reactive infiltration at 1300 °C for 1 h in vacuum using a molten Zr2 Cu alloy and a newly designed partially-carburized W powder as raw materials. The as-synthesized composites consist of two major phases of W and ZrC, in which the content of W is 65 vol%. The reaction time needed to produce a fully densified W-ZrC bulk ceramic is distinctly shortened by this means, as contrasted with conventional WC/W or WC preforms. The microstructural evolution during reactive melt infiltration is investigated to obtain a better understanding of reaction mechanisms and mechanical properties of the W-ZrC composites derived by infiltrating Zr2 Cu alloy into partially carburized W preforms. The flexural strength, Young's modulus and fracture toughness for the W-ZrC composite are 554 MPa, 339 GPa and 9.7 MPa·m 1/2, respectively. Highlights: W-ZrC composites without residual WC were prepared by infiltrating molten Zr2 Cu into partially carburized W preforms. The reaction time needed to produce a fully densified W-ZrC bulk ceramic is distinctly shortened. The flexural strength and fracture toughness for the W-ZrC composite are 554 MPa and 9.7 MPa·m 1/2, respectively.